The Nature of Humanity in the Perspective of Islamic Educational Philosophy - Romi Maulana; Maspuroh; Aliman Al Falah; Siti Khoerunnisa; Syifa Nuriah (Classroom: Journal of Islamic Education, 2025)
Humans are creatures created by Allah SWT. eho are equipped with reason, thoughts, feelings and beliefs to improve the quality of their life in the world so that they can be differentiated from other creatures (animals). Humans also have the highest rank among his other creations. Islamic education is a process related to the activities of preparing and developing all human potential and developing all human potential optimally. The islamic view of humans can be seen in four aspects, namely humans as noble creatures, humans as caliphs of Allah SWT. on this earth, humans are responsible creatures and humans are educated and educated creatures.